O RGANIZATION OF WORK OF NURSING IN FAMILY HEALTH STRATEGIES OF THE CITY OF CÁCERES - MT - Sylvia Maria Barbosa Cunha; Rosane Maria Andrade Vasconcelos; Danyella Rodrigues de Almeida; Eva Couto Garcia; Vânia Deluque AguilaR (Revista Gestão & Saúde, 2013)
The primary care team should be able to plan, organize, develop and evaluate actions that respondto community needs and articulate the various sectors involved in health promotion. Knowing theprofile of these professionals can take steps towards their qualification and performance, for a moreadequate assistance and quality of the population.Objective:Learn to Work OrganizationStrategies in Nursing Family Health Cáceres-MT.Methodology:This is a quantitative andqualitative research.Data collection occurred through questionnaires given to professional nursesand nursing technicians FHT the city of Cáceres, between the months of September and October2011.Result:We found that the relationship between professional community and currently is aprocess that is weakened. They state that almost always feel satisfied with their freedom andautonomy at work. Indicate the main impediments that hinder the work, such as inadequate physicalinfrastructure, lack of financial resources, materials, procedures, drug shortages, low pay.Conclusion:Work organization means not only reflect the way work is designed and ordered, butthink of all that makes up thiscontext and their social integration